The Training of Implementing Artificial Intelligence, Machine Learning and Big Data in Cloud Computing - Suranegara, Galura Muhammad; Jayadinata, Asep Kurnia; Nikawanti, Gia; Ichsan, Ichwan Nul; Ash Shiddiq, Reza Nurfaudzan; Faudzan, Muhammad Iqbal; Syaifullah, Muhammad Wildan; Kheqal, Abdul; Dinata, Hane Yorda (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2025)
Disruption is an inevitable consequence of rapid technological advancements. It occurs when existing human resources struggle to keep pace with the swift evolution of technology. One effective way to address this issue is by organizing training sessions aimed at enhancing skills. The Telecommunications Systems Study Program successfully held a training event designed to improve participants' skills, particularly in technology. The participants, including students from vocational high schools (SMK), expressed high levels of satisfaction with the event. The topics covered ranged from cloud computing, artificial intelligence, machine learning, to big data. The training did not merely provide theoretical knowledge but also included practical applications. This community service activity was organized by students serving as the event infrastructure team, with faculty members leading the event as the organizing committee. The participants were students from ten different vocational high schools (SMK) and took place over a period of one day, from 8 AM to 3 PM. Thanks to this training method, the student development significance value reached 33%.